Microstructure transformation due to hydrolytic degradation of ethylene terephthalate/lactic acid copolyesters - Grzebieniak, K.; Ślusarczyk, C.; Włochowicz, A.; Janicki, J. (Polimery, 2022)
Wide-angle (WAXS) and small-angle (SAXS) X-ray scattering methods have been used to study the supermolecular structure of ethylene terephthalate and lactic acid copolyesters having different chemical structure of macromolecules. The effect of copolymers chemical structure on their microstructure was investigated using crystallized (annealed) polymer samples. It as been found that the crystalline phase in the copolyesters ontains mainly PET segments (ET sequences). The degree of rystallinity decreases with lowering the length of (ET)(x) equences ((X) over bar values). The crystallized copolymers of ufficiently long ET sequences showed lamellar structure (long eriod reflex) in SAXS studies. Copolyester specimens in form f monofilaments ("as spun" as well as annealed) were subjected o hydrolytic degradation at pH 7.35 and temp. 60degreesC over time period of up to 9 weeks. Intensity of degradation hanges (eta(red) and weight of the specimens) as well as intensity and nature of microstructure changes (WAXS and SAXS data) were highly dependent on chemical structure of the copolymers. Microstructure changes, especially SAXS characteristics, were also highly dependent on the initial morphology of the specimens, i.e. on whether they were crystallized or not before degradation.